Finite Element Analysis of Meshing Stiffness of Harmonic Gear - Wei Leyu; Wang Changlu; Zhang Liyong; Liu Xinmeng; Qiao Xuetao; Wang Ruifeng (Jixie chuandong)
The calculation of harmonic gear meshing stiffness is the basis of dynamics analysis. According to the finite element analysis theory of loading contact,and combining with its static and dynamic contact properties,taking each different location during one engaging-in and engaging-out cycle of a tooth as the research object. Then,by extracting the meshing data of discrete point on contact location,the curve of single-tooth stiffness and the synthesizing meshing stiffness in one engaging-in and engaging-out is got. Comparing with the previous researching result,the correctness of the method is verified,which provides the basis for dynamics analysis for harmonic gear.